Passing Recipes: How Users’ Innovations are Distributed - Bogatyr, Natalia (Journal of Economic Sociology, 2013)
This article focuses on the “domestication” of hard disk drives’ technologies and the development of data recovery market in Post-Soviet Russia. Drawingon 3,5 years ethnographic research with one data recovery service center in Moscow, as well as on 12 in-depth narrative semi-structured interviews with technicians in Moscow, Saint Petersburg, Rostov-on-Don and Minsk, the authorargues that lead users were centre players in these developments. The author narrows and specifies E. von Hippel’s definition of lead users, stressing as main characteristics their abilities to invent and to materialize their inventions to create new marketplaces through commercialization of their technological innovations (or, in other words, the ability to complete an innovation cycle by themselves). The questions the author poses in this article are: 1) Who were those lead users that invented data recovery as a new service in Russia? 2) In which directions did they transfer their innovations? 3) Which ways and means did they use? To address these questions, the article proceeds through five sections and examines the social basis of data recovery and the history of this field; the practices of transferring innovation vertically (to producers; “invention”), horizontally (to other lead users; “objectification”) and downwards (to domesticusers; “commercialization”); the dynamics of data recovery as a “cultural recipe”. To analyze data, the author has adopted some grounded theory techniques, thus the result of my undertaking is a “theory” which explains data recovery market development as an evolution of users’ cultural recipes. The article concludes with an assumption that, in Russia, certain innovations in other commercial or industrial fields (for example,automobile electronics) could be initiated by lead users and organized along similar lines to data recovery.